Electron source and acceleration regime of a picosecond electron beam in a gas-filled diode with inhomogeneous field; Technical Physics Letters; Vol. 34, № 2 - Mesyats G. A. Gennady Andreyevich; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2008, 2008)
В фонде НТБ ТПУ отсутствует